FIRST RECORD OF NATURALIZED ACMELLA BRACHYGLOSSA AND ACMELLA RADICANS (ASTERACEAE: HELIANTHEAE) IN JAVA, INDONESIA - Zakaria Al Anshori; Arifin Surya Dwipa Irsyam; Asih Perwita Dewi; Muhammad Rifqi Hariri; Peniwidiyanti Peniwidiyanti; Rina Ratnasih Irwanto (Floribunda, 2022)
Acmella brachyglossa and A. radicans are introduced species native to Central and South America. Here, both species are formally reported for the first time in Java. Acmella brachyglossa is characterized by its pale yellow-colored heads and has 5‒8 ray flowers. Meanwhile, A. radicans has discoid heads, 4-merous flowers, and white-coloured. Acmella brachyglossa was collected from West Java (Sumedang Regency and Bogor Regency). While A. radicans was found in West Java (Bandung Regency, Bandung City, Sumedang Regency) and Central Java (Temanggung Regency). Descriptions, illustrations, a key to Acmella of Java, and a brief discussion are presented in this paper.